2022
DOI: 10.37689/acta-ape/2022ao0390345
|View full text |Cite
|
Sign up to set email alerts
|

Funcionalidade, estresse e qualidade de vida de sobreviventes de acidente vascular encefálico

Abstract: ResumoObjetivo: Correlacionar a capacidade funcional e o estresse percebido com a qualidade de vida relacionada à saúde de sobreviventes de acidente vascular encefálico.Métodos: Estudo analítico transversal, realizado com 160 sobreviventes de acidente vascular encefálico cadastrados em Unidades de Saúde da Família. Os dados foram coletados mediante a utilização de um instrumento semiestruturado para obtenção dos dados sociodemográficos e de saúde, o Índice de Barthel, a Escala de Estresse Percebido e a Escala … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A study found, in a sample of 160 stroke survivors, that most participants had low health-related quality of life, with greater impairment in Social role (socialization with friends, sexual relations and interference of physical condition in social life) and Family role (fun with family, feeling of being a burden on family members and influence of physical condition on personal life) domains, as well as association with reduced ability to return to work (absence of work occupation), sedentary lifestyle, functional dependence, presence of caregiver, motor sequel and lack of rehabilitation after hospital discharge ( 19 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study found, in a sample of 160 stroke survivors, that most participants had low health-related quality of life, with greater impairment in Social role (socialization with friends, sexual relations and interference of physical condition in social life) and Family role (fun with family, feeling of being a burden on family members and influence of physical condition on personal life) domains, as well as association with reduced ability to return to work (absence of work occupation), sedentary lifestyle, functional dependence, presence of caregiver, motor sequel and lack of rehabilitation after hospital discharge ( 19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…J4 said that COAP-AVC is "Excellent for both patients and professionals". Family role (fun with family, feeling of being a burden on family members and influence of physical condition on personal life) domains, as well as association with reduced ability to return to work (absence of work occupation), sedentary lifestyle, functional dependence, presence of caregiver, motor sequel and lack of rehabilitation after hospital discharge (19) .…”
Section: Content Analysis -Second Roundmentioning
confidence: 99%